Sistema Único de Saúde: redução das funções públicas e ampliação ao mercado - Tânia Regina Krüger (e-cadernos ces)
This text aims to discuss the tensions in the relationship between the public and the private sectors in the Brazilian Unified Health System (UHS). The celebrations of the 30th anniversary of the UHS took place in a political conjuncture in which the country was facing an unprecedented setback in the political and institutional process and a disintegration of the guarantee of citizenship rights. Assuming an exploratory nature, the study was based on a bibliographical and documentary review of UHS regulations. It deals with counter-reforms that have been striking the UHS since its inception and displays indicators of how it has become functional to the private health sector. All this critical analysis does not disregard the fact that the UHS has built relevant public services and that it is one of the most important achievements in social policies for democratic and popular struggles, and can therefore be considered a national heritage.